2021
DOI: 10.1016/j.isci.2021.102910
|View full text |Cite
|
Sign up to set email alerts
|

Shigella OspC3 suppresses murine cytosolic LPS sensing

Abstract: Summary Shigella flexneri , a cytosol-invasive gram-negative pathogen, deploys an array of type III-secreted effector proteins to evade host cell defenses. Caspase-11 and its human ortholog caspase-4 detect cytosolic lipopolysaccharide (LPS) and trigger gasdermin D-mediated pyroptosis to eliminate intra-cytoplasmic bacterial threats . However, the role of caspase-11 in combating S. flexneri is unclear. The Shigella T3S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 63 publications
3
28
0
Order By: Relevance
“…Shigella also deploys an effector, IpaH7.8, which degrades human (but not mouse) GSDMD to block pyroptosis, further underscoring the importance of this axis in defense (Luchetti et al, 2021). We note that CASP11-dependent protection is not sufficient to render ospC3-infected B6.Nlrc4 -/mice completely resistant to disease symptoms, perhaps because the priming required to induce CASP11 expression might delay its protective response (Oh et al, 2021).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Shigella also deploys an effector, IpaH7.8, which degrades human (but not mouse) GSDMD to block pyroptosis, further underscoring the importance of this axis in defense (Luchetti et al, 2021). We note that CASP11-dependent protection is not sufficient to render ospC3-infected B6.Nlrc4 -/mice completely resistant to disease symptoms, perhaps because the priming required to induce CASP11 expression might delay its protective response (Oh et al, 2021).…”
Section: Discussionmentioning
confidence: 84%
“…Shigella flexneri protein OspC3 is a T3SS-secreted effector that inhibits both human Caspase-4 and mouse Caspase-11 to suppress pyroptosis (Kobayashi et al, 2013; Li et al, 2021; Mou et al, 2018; Oh et al, 2021). While OspC3 has been shown to be required for virulence during intraperitoneal mouse infection (Li et al, 2021; Oh et al, 2021) and for intestinal lumenal colonization in wild-type mice (Alphonse et al, 2022), the role of this effector has not been studied in an oral mouse model of infection where Shigella invades and replicates within the intestinal epithelium. Indeed, our results indicating a role for Caspase-11 in defense against wild-type Shigella (see above, Figures 1 and 2) suggested that the inhibition of Caspase-11 by OspC3 could be incomplete in epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of several effectors (blue bars) led to IFN inhibition at a level comparable with that mediated by NSP2 (Figure 1D). We chose to follow up on the OspC effector family that had previously been shown to modulate immune pathways (Ashida et al, 2020;Kobayashi et al, 2013;Li et al, 2021;Miller et al, 2018;Mou et al, 2018;Oh et al, 2021;Zurawski et al, 2006).…”
Section: Shigella Effectors Block Isg Expressionmentioning
confidence: 99%
“…This illustrates the potent defense conferred by pyroptosis and autophagy against pathogens that have intermediate or even high virulence potential, but which lack the ability to inhibit these defenses. Shigella is a pathogen with high virulence that additionally can inhibit these defenses ( 40 , 41 ). Shigella dysenteriae and Shigella flexneri cause the disease Shigellosis, which is characterized by hemorrhagic diarrhea and is particularly dangerous to young children ( 42 , 43 ).…”
Section: Shigella and Inhibition Of Pyroptosismentioning
confidence: 99%